A quantitative study on the factors influencing the credit card usage among Bank Islam customers in Taman Tun Dr. Ismail (TTDI), Kuala Lumpur / Ahmad Fadil Abdul Halim - Abdul Halim, Ahmad Fadil (Faculty of Business and Management, 2014)
This research was conducted to identify the possible factors that may influence the credit card usage among Bank Islam customers in Taman Tun Dr. Ismail (TTDI), Kuala Lumpur. There are three independent variables that were used in this study, which are financial knowledge, personal value and media awareness. The objectives of this study is to identify the factors that influence the credit card usage among Bank Islam customers in TTDI, KL, to examine the relationship between financial knowledge and credit card usage, to examine the relationship between personal value and credit card usage and to examine the relationship between media awareness and credit card usage. The questionnaires were randomly distributed to 50 walk-in Bank Islam customers in TTDI, KL. The results show that there are no significant relationship between all the independent variable and the dependent variable. This is most probably because of the independent variables used in this study are not suitable for those who live in the city and have an urban lifestyle. As a suggestion, maybe for the future study the researcher can focus and use these independent variables in a smaller area or small town such as Tanjung Malim.